Effect of equal channel angular pressing on thermal and mechanical properties of carbon nanotube/high density polyethylene composite. (2nd October 2017) - Mokarizadeh Haghighi Shirazi, Majid; Zebarjad, Seyed Mojtaba; Ebrahimi, Ramin
Abstract : High density polyethylene (HDPE) nanocomposite reinforced with 2 weight percent carbon nanotube (CNT) was fabricated using mechanical milling method. Microscopic evaluations revealed appropriate dispersion of CNTs in the matrix, and tensile tests demonstrated that the tensile strength was increased by 17%. Thermal and mechanical properties of the composite samples were investigated after equal channel angular pressing (ECAP) for up to 3 passes via route A at temperature of 80°C. Density and differential scanning calorimetry (DSC) results represented decrement in crystallinity after ECAP which was led to drop in hardness and tensile yield strength of the deformed samples. Micro Vickers and Shore D hardness results also revealed clear anisotropy in mechanical properties caused by ECAP. Dilatometry results and observation of the impact fractured surfaces of deformed samples demonstrated that oriented structures formed in amorphous and crystalline regions of the composite. This microstructure evolution also caused increase in impact strength of ECAP deformed specimens. Dynamic mechanical behavior of the processed samples was modified following ECAP. The α and γ relaxation temperatures were decreased due to the reduction of thickness of crystalline lamella obtained from DSC results, in 1 pass ECAP deformed sample. Dynamic storage and loss modulus of 3 passes ECAP deformed samples were significantly decreased due to the sharp drop in their crystallinity.